Knowledge and perception of students towards Trichomoniasis at Ekwendem Girls Secondary School. - Mtegha, Thandie (Kamuzu University of Health Sciences, 2022)
Globally, trichomoniasis is less known and receives far less attention. In Malawi, trichomoniasis is very common in girls' boarding secondary schools. The aim of the study is to assess knowledge and perception of students towards trichomoniasis at Ekwendeni Girls' Secondary School in Mzimba district. The specific objectives of the study include: To assess existing knowledge of students on trichomoniasis. To explore ways students can use to prevent trichomoniasis. To find out the accessibility of information among students on trichomoniasis. The study will use qualitative research design. A sample of 10 students will be recruited 1 using convenient sampling. In-depth interviews will be used to collect data using an interview guide. The rights of the participants and other ethical issues will be considered during the study. Data will be analysed manually and the findings of the study will be disseminated at KCN library and Ekwendeni Girls' Secondary School.